2008
DOI: 10.1186/1471-244x-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neural synchronization of gamma-band MEG oscillations in first-degree relatives of children with autism

Abstract: Background: Gamma-band oscillations recorded from human electrophysiological recordings, which may be associated with perceptual binding and neuronal connectivity, have been shown to be altered in people with autism. Transient auditory gamma-band responses, however, have not yet been investigated in autism or in the first-degree relatives of persons with the autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
165
10
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(193 citation statements)
references
References 57 publications
(59 reference statements)
14
165
10
1
Order By: Relevance
“…Rojas, Maharajh, Teale & Rogers, 2008) whereas other studies have found no difference in evoked (Gandal et al 2010;Wright et al 2012) or induced gamma power (Gandal et al 2010). Here, we found no significant difference in either evoked or induced peak gamma power between the participants with and without ASC.…”
Section: Differences (See Dickinson Et Al 2014 For a Full Discussion)contrasting
confidence: 82%
“…Rojas, Maharajh, Teale & Rogers, 2008) whereas other studies have found no difference in evoked (Gandal et al 2010;Wright et al 2012) or induced gamma power (Gandal et al 2010). Here, we found no significant difference in either evoked or induced peak gamma power between the participants with and without ASC.…”
Section: Differences (See Dickinson Et Al 2014 For a Full Discussion)contrasting
confidence: 82%
“…Abnormalities in auditory-evoked γ-oscillatory activity have been observed in schizophrenia as well as other neuropsychiatric disorders such as autism (3,7,10,(46)(47)(48). To test for disruptions in oscillatory activity during the evoked response in the Dys1 −/− mice, EEG trials were wavelet-transformed to extract instantaneous power and phase over all frequencies from θ to γ (4-100 Hz) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evoked activity is both phase-locked and time-locked to the onset of a stimulus; induced activity often occurs later than evoked activity, and whilst it is time-locked it is not phase-locked to the stimulus. While several studies have found evoked gamma band power to be reduced in ASD (Edgar et al, 2015;Baruth et al, 2010;Rojas, Maharajh What do changes in evoked and / or induced gamma band power suggest about E/I balance in ASD? There is little existing data that allows us to confidently link evoked gamma power to E/I balance, although one study suggests that evoked gamma power may be associated with glutamate levels, as Lally et al (2014) have reported a positive correlation between dynamic glutamate levels (measured using MRS) and evoked gamma band power (measured using EEG recorded from parietal and occipital electrodes; Lally et al, 2014).…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 99%